The Ubiquitin Ligase TRAF6 Negatively Regulates the JAK-STAT Signaling Pathway by Binding to STAT3 and Mediating Its Ubiquitination - Wei, Juncheng (Public Library of Science, 2012)
STAT3 is a key transcription factor that mediates various cellular and organismal processes, such as cell growth, apoptosis, immune response and cancer. However, the molecular mechanisms of STAT3 regulation remain poorly understood. Here, we identified TRAF6 as a new STAT3 interactor. TRAF6 augmented the ubiquitination of STAT3 and deactivated its transcriptional activity induced by IFNα stimulation or overexpressed with JAK2. Both the RING domain and the TRAF-type zinc finger domain of TRAF6 were indispensable for STAT3 deactivation. Accordingly, TRAF6 also down-regulated the expression of two known STAT3 target genes, CRP and ACT. Therefore, we showed that TRAF6 is a new regulator of JAK/STAT signaling and provide a new mechanistic explanation for the crosstalk between the NF-κB and the JAK-STAT pathways.